Plan de negocio para la creación de un centro de acondicionamiento infantil en la ciudad de Quito - Bracho Villavicencio, Priscila Alejandra (2014)
The business plan involves the creation of a fitness center for children in Quito Canton, it consists in the implementation of training programs for children from 3 to 11 years old; these programs accomplish each energetic necessity profile. The objective in the creation of this center goes beyond fighting children obesity, it pretends to give an integral formation to its clients, powering their physical, psychological and cognitive capabilities based on these three main foundations: psychomotor, physical activities and brain gym therapies. As today in Ecuador, there aren’t any children care centers which englobes the foundations mentioned above; in Latin America the idea of gyms for children has evolved, in Mexico for example, sales raised a 30 percent and in Chile, in just two years, more than 15 gyms has been established for this target. What makes this business different is that it answers mother’s desires of raising brilliant children by the means of specialized personnel in key areas; having unique and innovative machinery makes this business a market pioneer. Target market size is of 29981 mothers, with an objective of grabbing a 1 percent market share that is 300 mothers. At the end of a five year projection it’s expected to grab 0.75 percent of this share, with a maximum capacity installed of 225 members monthly, and incomes that surpass the USD 200000 milestone in the last years of this projection, with a utility margin of 39.7 percent and a ROI of 118 percent at the end of the fifth year. Initial Investment, including the working capital necessary to put the current business plan to work is USD 94233.70. The financial analysis done has been projected for the next five years; net present value is USD 54281.05. These money flows were calculated with CAPM model, in which, capital initial cost is percent 20.7, discount rate is 18.2 percent and rate of return of this project is 29.6 percent.